Elemental Composition of Particulate Matter in the Southeastern Brazilian Ceramic Pole by Synchrotron Radiation X-ray Fluorescence Technique (SR-XRF) - Dourado, Thiago [UNESP]; Gemeiner, Hendryk [UNESP]; Gomes, Ana Carla F.; Almeida, Eduardo; Silva, Adivania C. da; Valadao, Nayara; Menegario, Amauri Antonio [UNESP]; Govone, Jose Silvio [UNESP]; Gastmans, Didier [UNESP] (Soc Brasileira Quimica, 2020)
In the present study, the elemental content of the particulate matter PM2.5 (particulate matter with diameters lower than 25 gm) and PM10 (particulate matter with diameters lower than 10 mu m) of the Brazilian city of Rio Claro (SP) were analyzed by synchrotron radiation X-ray fluorescence (SR-XRF) in the Brazilian Synchrotron Light Laboratory (LNLS). A fractional sampling of particulate matter (PM) was carried out in two climatic periods (dry and rainy season). The elemental determination of PM2.5 and PM10 included the following elements: Si, S, Ca, K. Ti. Cr. Mn, Fe, Cu, and Zn. Elemental correlation studies, cluster analysis, principal component analysis and enrichment factor determination were performed in order to allow the distinction of the main sources of the emission of PM. The mean elementary contents, especially in PM10. were statistically different to each other between the sampling seasons and higher in dry than in rainy season. The cluster analysis indicated two groups as being the main constituting element groups for the composition of PM in Rio Claro. A major group originated by the resuspension of soil composed by the elements Si, Fe, Ca and K. and a second, minor group composed of S, Ti, Mn. Cu, Cr, and Zn, presumably influenced by vehicular emissions and the regions adjacent ceramic industries.
Keywords: particulate matter; synchrotron radiation; X-ray fluorescence; emission sources; ceramic pole